The AI516 and AI523 antibodies recognize the Klebsiella pneumoniae KpGe strain by flow cytometry - Crespo-Yanez, Xenia; Ayadi, Imen (Antibody Reports, 2022)
The recombinant antibodies AE516 and AI523 bind to the surface of the Klebsiella pneumoniae KpGe strain, as detected by flow cytometry. They do not bind to a K. pneumoniae strain defective in O-antigen synthesis.